A Study on Felling and Conversion of Pulpwood - Mitra, S. K.; Sood, K. G. (Indian Forester, 1979)
A comparative study was designed and conducted to find out the best economic hand tool for felling, cross cutting, delimiting for the preparation of unbarked pulpwood billets. For these operations six type of saws including power chain saw were used in Bijnor Plantation Division of U.P. for felling and conveuion of Eucaiyplus hybrid. The Investigation on was carried out in two phases It was observed that under existing condition power chain saw is not economical for pulpwood harveoting. The best tool appears to be scientifically maintained peg tooth cross cut saw. It was also observed that scientific maintenance of saws increases the efficiency of the tool by 54% and consequently the production cost is substantially decresaed.